Management Foundations and Global Readiness Index of School Heads of the Philippines - Baliton, Fructuoso C. (JPAIR Multidisciplinary Research, 2012)
An understanding of personality contributes to an understanding of organizational behavior in that we expect a predictable interplay between an individual’s personality and his or her tendency to behave in certain ways (Jacob 1995). Most organizations today must achieve high performance in the context of a competitive and complex global environment (Porter 1998). This descriptive survey correlation method of research aimed to determine whether the management foundations of secondary school heads were related to their global readiness index. The findings of this study may serve as a basis to take their strong personal characteristics as skills that should be nurtured and to take their good points as starting points to consider where and how to further pursue the development of their managerial skills and competencies. This may also serve as a feedback to work hard to grow and develop continually in the management foundations considering that their successes as 21st century managers may well rest on an initial awareness of the importance of these basic management foundations and that they must be comfortable with the global economy and the global diversity that it holds. Chi-square established that their management foundations are not significantly related to their global readiness index.